Depression and risk of hospitalisations and rehospitalisations for ambulatory care-sensitive conditions in Denmark: a population-based cohort study. Issue 12 (2nd December 2015) - Davydow, Dimitry S; Fenger-Grøn, Morten; Ribe, Anette Riisgaard; Pedersen, Henrik Søndergaard; Prior, Anders; Vedsted, Peter; Unützer, Jürgen; Vestergaard, Mogens
Abstract : Objective: Hospitalisations for ambulatory care-sensitive conditions (ACSCs), a group of chronic and acute illnesses considered not to require inpatient treatment if timely and appropriate ambulatory care is received, and early rehospitalisations are common and costly. We sought to determine whether individuals with depression are at increased risk of hospitalisations for ACSCs, and rehospitalisation for the same or another ACSC, within 30 days. Design: National, population-based cohort study. Setting: Denmark. Participants: 5 049 353 individuals ≥18 years of age between 1 January 2005 and 31 December 2013. Measurements: Depression was ascertained via psychiatrist diagnoses in the Danish Psychiatric Central Register or antidepressant prescription redemption from the Danish National Prescription Registry. Hospitalisations for ACSCs and rehospitalisations within 30 days were identified using the Danish National Patient Register. Results: Overall, individuals with depression were 2.35 times more likely to be hospitalised for an ACSC (95% CI 2.32 to 2.37) versus those without depression after adjusting for age, sex and calendar period, and 1.45 times more likely after adjusting for socioeconomic factors, comorbidities and primary care utilisation (95% CI 1.43 to 1.46). After adjusting for ACSC-predisposing comorbidity, depression was associated with significantly greater risk of hospitalisations for all chronic (eg, angina, diabetes complications, congestive heart failure exacerbation) and acute ACSCs (eg, pneumonia) compared to those without depression. Compared to those without depression, persons with depression were 1.21 times more likely to be rehospitalised within 30 days for the same ACSC (95% CI 1.18 to 1.24) and 1.19 times more likely to be rehospitalised within 30 days for a different ACSC (95% CI 1.15 to 1.23). Conclusions: Individuals with depression are at increased risk of hospitalisations for ACSCs, and once discharged are at elevated risk of rehospitalisations within 30 days for ACSCs.